Effects of Cefepime Versus Doxycycline on Alveolar Bone Loss and Gingival Re-cession in Smoker Dental Patients: Clinical Trial - Fayhaa AM Al-Mashhadane (University of Mosul, College of Dentistry, 2011)
Aims: To determine the prevalence and severity of attachment loss and bone loss among smokers and to compare them with non smokers and to assess the effect of cefepime compared to doxycycline in the outcomes of healing of these periodontal diseases in smoker patients. Materials and Methods: This study was carried out on 80 patients, half of which were smokers(40) and the other were nonsmokers, aged from 20 - 50 years, attending the teaching dental clinics in the College of Dentistry, University of Mosul. Questionnaire of smoking habit was applied on smoker patients. Clinical measurements were done including attachment loss and carried out according to Ramfjord gingival sulcus measurement index, Bone loss was measured radiographically with an x - ray unit. A total of 40 smoker patients were received supportive periodontal therapy and then randomly divided into 2 groups, first group (20 patients) were treated by cefepime powder mixed with distilled water and second group (20 patients) were treated by doxycycline powder mixed with distilled water. Both drugs were injected into peri-odontal pocket and remained in the oral cavity for 15 min then rinsed with distilled water. Each patient receive one session of treatment / once a week for 6 months. Clinical and ragiographical parameters of attachment and bone loss were measured at baseline , 2, 4 and 6 months recall visits. Results: Un-paired t - test was used for statistical analysis of the data and there were significant differences of at-tachment loss (p≤ 0.000) and bone loss (p≤ 0.001) between smoker and non smokers . There were no significant differences between smokers treated with cefepime compared to those treated by doxycyc-line for attachment loss (before treatment p≤0.893, after treatment p< 0.668) and for bone loss (before treatment p<1.000, after treatment p< 0.849). Conclusions: Tobacco use is an important variable af-fecting the health of periodontal tissues. Topical application of antimicrobial agents at the site of peri-odontal diseases may be a useful adjunct to the conventional periodontal treatment.